Role of Ca2+ Homeostasis Disruption in Rotavirus-Associated Seizures. (March 2014) - Yeom, Jung Sook; Kim, Young-Soo; Park, Ji Sook; Seo, Ji-Hyun; Park, Eun Sil; Lim, Jae-Young; Park, Chan-Hoo; Woo, Hyang-Ok; Youn, Hee-Shang
Rotavirus infection disturbs cellular Ca 2+ homeostasis by triggering an increase in Ca 2+ permeation. A theoretical link between Ca 2+ dysregulation and seizures in patients with rotavirus gastroenteritis has been suggested, but no prior studies have investigated this relationship. To test our hypothesis that patients with rotavirus-associated seizures have greater Ca 2+ homeostasis disruption than those without seizures, we compared clinical and laboratory data—including corrected total serum Ca 2+ levels—between the 2 groups. Age, gender, maximum body temperature, day of admission, levels of electrolytes except Ca 2+, blood pH, and urine ketone levels were not related to seizure occurrence. Significantly lower Ca 2+ levels were found among the seizure (+) group (9.22 ± 0.50 vs 9.66 ± 0.46 mg/dL, P = .01). Although Ca 2+ levels were within normal ranges and did not directly cause the seizures, our results provide preliminary evidence for a relationship between Ca 2+ homeostasis disruption and seizures in rotavirus patients.